Fatigue Analysis of a Railway Steel Bridge - Viswanatj, Kandagatla; Ravi Kumar, M (International Journal of Engineering and Technology, 2018)
One of the significant means of transportation in India are railways and has many steel bridges which are very old having historical importance and their design period is terminating. To appraisal, the levels of damage for workable repairs, stands a tedious job for government authorities. The prediction of fatigue life of bridges are important because at present these are subjected to elephantine loads than the design loads and the environmental conditions boost these aspects to turn up fatigue life. This paper studies the analytical analysis of a steel railway bridge subjected to EURO and INDIAN fatigue loading to evaluate the fatigue life of a bridge and stresses are calculated from S-N curves by nominal stress method. The fatigue verification has been done by Î»-coefficient method. Fatigue life of critical section was found out by sub-modelling the welded joint where the stress are maximum. The crack initiation starts at powerless members and propagates it along the section leads to fracture the entire structure under elastic behaviour. Hence, if the results of the critical section are satisfactory, it can be concluded that entire bridge is safe in fatigue point of view. INDIAN HM loadings generate more damage than EURO LM-71 loading.Â Â